Management of a Severely Submerged Primary Molar: A Case Report - Iman Parisay; Fatemeh Kebriaei; Bentolhoda Varkesh; Milad Soruri; Roya Ghafourifard (Case Reports in Dentistry)
Ankylosis is a condition frequently associated with primary molars, wherein the ankylosed primary teeth remain in a fixed position, while the adjacent teeth continue to erupt, moving occlusally. In this case report, a five-year-old boy, who had a retained and submerged left lower second primary molar, was presented. Luxation of ankylosed primary molar was considered as a treatment approach. After four months, the tooth erupted to the occlusal level, and there was evidence of further development of a permanent successor in radiographic evaluation. After one year, tooth mobility, bone formation, and development of a permanent successor were in good condition.